1998
DOI: 10.1089/thy.1998.8.419
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Restriction in Thyroid Eye Disease

Abstract: Infiltrating immunocompetent cells act to establish and perpetuate the orbital autoimmune process in thyroid eye disease (TED). Until recently, it has remained unclear whether T cells infiltrating the orbital connective/fatty tissue and extraocular muscles represent a primary immune response that is specifically directed against orbital antigens. In addition, despite a close clinical and temporal association of the thyroidal and extrathyroidal manifestations in Graves' disease (GD), it has not been proven whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…After infiltration of the orbit by T cells, the shared antigen could then be recognized by a T cell receptor on CD4ϩ T lymphocytes: the finding of a biased usage of the T cell receptor variable gene (14,15) supports the concept of an antigen-specific immune reaction (9). After antigen recognition, CD4ϩ T lymphocytes could secrete cytokines that amplify the immune reaction by either activating CD8ϩ T lymphocytes or autoantibody-producing B cells (16).…”
Section: Pathogenesismentioning
confidence: 88%
“…After infiltration of the orbit by T cells, the shared antigen could then be recognized by a T cell receptor on CD4ϩ T lymphocytes: the finding of a biased usage of the T cell receptor variable gene (14,15) supports the concept of an antigen-specific immune reaction (9). After antigen recognition, CD4ϩ T lymphocytes could secrete cytokines that amplify the immune reaction by either activating CD8ϩ T lymphocytes or autoantibody-producing B cells (16).…”
Section: Pathogenesismentioning
confidence: 88%
“…Graves' ophthalmopathy, or thyroid eye disease (TED) 58,59 , is the most frequent extrathyroidal clinical manifestation of Graves' disease and constitutes a major and complex pathogenetic and therapeutic dilemma 26 . The first possible connection between cigarette smoking and Graves' ophthalmopathy was made by Hagg and Asplund 60 who showed that 10 out of 12 patients were current smokers, a figure much higher than that observed in Graves' patients without ophthalmopathy (46%) or in control subjects (31%).…”
Section: B Graves' Ophthalmopathymentioning
confidence: 99%
“…Development of diversity or polyclonality of the TCR gene repertoire indicates that orbital inflammation is at the burnout stage. Heufelder summarized data from three severe active GO patients with GD and dermopathy and reported not only marked TCR restriction, but also several conserved junctional motifs shared by T cells in the orbit, thyroid, and pretibial tissue despite obvious heterogeneity of the TCR genes in each patient ( 12 , 51 ). This highlights the presence of certain oligoclonal T cell populations stimulated by the analogous antigenic determinants shared by the thyroid and the involved extrathyroidal compartments.…”
Section: Self-reactive T Cells Directed Against Ofsmentioning
confidence: 99%